(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Systemic hypertension is a major risk factor for cardiovascular, cerebrovascular, and renal diseases. Persistent elevated blood pressure causes retinal microvascular changes collectively known as hypertensive retinopathy. Retinal examination provides a non-invasive method for assessing vascular damage and target organ involvement in hypertensive patients. The present study aimed to evaluate the association between systemic hypertension and retinal vascular changes in adults attending a tertiary care hospital. Methodology: This hospital-based cross-sectional study was conducted in the Department of General Medicine at Sree Mookambika Institute of Medical Sciences from January 2025 to January 2026. A total of 200 hypertensive patients were included. Blood pressure was measured using standard methods and patients were categorized as controlled or uncontrolled hypertension. Detailed ophthalmologic examination and fundus photography were performed after pupillary dilatation. Retinal changes were graded according to the Keith–Wagener–Barker classification. Statistical analysis was performed to determine associations between hypertension and retinal vascular changes. Results: Among 200 patients, 67% showed evidence of hypertensive retinopathy. Grade 1 retinopathy was the most common finding (36%), followed by Grade 2 (21%), Grade 3 (8%), and Grade 4 (2%). Severe retinopathy was observed exclusively in uncontrolled hypertensive patients (p<0.001). Longer duration of hypertension was significantly associated with increased severity of retinal vascular changes. Conclusion: Hypertensive retinopathy is strongly associated with uncontrolled and long-standing hypertension. Retinal examination is a valuable non-invasive tool for early detection of vascular damage and assessment of systemic complications in hypertensive patients.